Qualitative Study: Ethical Standards and Patient Rights - Ummul Hairat; Melda Ningsih Sibela (GLOBAL HEALTH SCIENCE GROUP, 2026)
In the era of health transformation following the enactment of Law Number 17 of 2023, hospitals are faced with the significant challenge of integrating ethical standards and patient rights protection into real-world service practices. As a referral hospital with high patient dynamics, Al-Fatah Ambon General Hospital requires an internal evaluation mechanism to ensure that administrative policies are aligned with implementation in the field. This study aims to analyse the effectiveness of the implementation of ethical standards and patient rights through a self-assessment method. This study uses a descriptive qualitative approach with a thematic analysis design. Data were collected through semi-structured interviews with five key informants: the Head of Personnel, personnel staff, HRD, Head of Training, and the Secretariat. Data collection used a semi-structured interview technique. Data were collected using a self-assessment instrument. The data analysis technique employed was thematic analysis, then compared and synchronised with the latest national regulations, particularly Law No. 17 of 2023. The study findings reveal a high level of compliance, with an average score exceeding 85%. Al-Fatah General Hospital achieved a perfect score (100%) in the aspects of complaint handling and understanding of managerial ethics. This success was driven by the transparency of its no-down-payment emergency financing policy and ethical leadership that prioritises patient safety over administrative procedures. Al-Fatah General Hospital Ambon has successfully internalised ethical standards and patient rights in accordance with the latest national regulations. A strong internal oversight system and a responsive complaint handling mechanism are key to maintaining service quality and public trust.